In Situ Fabrication of Silver Nanoparticle‐Decorated Polymeric Vesicles for Antibacterial Applications - Fen Zhang; Qian Yao; Yanling Niu; Xiaoqi Chen; Haijun Zhou; Lu Bai; Zejuan Kong; Yantao Li; Hua Cheng (ChemistryOpen, 2024)
Abstract Silver/polymeric vesicle composite nanoparticles with good antibacterial properties were fabricated in this study. Silver nanoparticles (AgNPs) were prepared in situ on cross‐linked vesicle membranes through the reduction of silver nitrate (AgNO3) using polyvinylpyrrolidone (PVP) via coordination bonding between the Ag+ ions and the nitrogen atoms on the vesicles. X‐ray diffraction (XRD), ultraviolet‐visible spectroscopy (UV‐vis), and transmission electron microscopy (TEM) analyses confirmed the formation of AgNPs on the vesicles. The antibacterial test demonstrated good antibacterial activity against both Gram‐negative bacteria (Escherichia coli) and Gram‐positive bacteria (Staphylococcus aureus) for the produced AgNP‐decorated vesicles. The minimum inhibitory concentration (MIC) values of the AgNP‐decorated vesicles for E. coli and S. aureus were 8.4 and 9.6 μg/mL, respectively. Cell viability analysis on the A549 cells indicated that the toxicity was low when the AgNP concentrations did not exceed the MIC values, and the wound healing test confirmed the good antibacterial properties of the AgNP‐decorated vesicles.